1998
DOI: 10.1007/bf02786511
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell signaling aberrations in human lupus

Abstract: A large array of heterogeneous aberrations of the immune system have been described in systemic lupus erythematosus (SLE). Since the function and the fate of the immune system cells are governed principally by the biochemical events that follow ligation of specialized cell-surface receptors, we will review in this article recent developments in our understanding of abnormalities in the biochemistry of signals generated either by the antigen-receptor complex or by systems of costimulatory cell-surface molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…Sloan-Lancaster et al reported that T cell anergy correlates with decreased levels of the p21 and p23 forms of the TCR chain (55). These results are also consistent with the finding that SLE patients have more anergic T cells compared with normal donors (1,56). The fact that the decrease in the 21-and 23-kd forms of the chain in SLE patients correlates well with the decrease in the level of the detergent-soluble 16-kd form of the chain ( Figure 2C) indirectly suggests that the decrease in the phosphorylated form is not the consequence of a defective phosphorylation cascade in SLE T cells.…”
Section: Discussionsupporting
confidence: 81%
“…Sloan-Lancaster et al reported that T cell anergy correlates with decreased levels of the p21 and p23 forms of the TCR chain (55). These results are also consistent with the finding that SLE patients have more anergic T cells compared with normal donors (1,56). The fact that the decrease in the 21-and 23-kd forms of the chain in SLE patients correlates well with the decrease in the level of the detergent-soluble 16-kd form of the chain ( Figure 2C) indirectly suggests that the decrease in the phosphorylated form is not the consequence of a defective phosphorylation cascade in SLE T cells.…”
Section: Discussionsupporting
confidence: 81%
“…ϩ Ts in the presence of autologous macrophages because these latter cells are needed to induce CD8 ϩ T lymphocyte suppressor function (22). However, macrophage cytokine secretion likely had a poor direct effect in determining inhibition of proliferation as suggested by the fact that counteraction of inhibition was possible only when CD8…”
Section: Discussionmentioning
confidence: 99%
“…3 is an autoimmune disease of unknown etiology that is characterized by multiple T cell signaling abnormalities (1). T cells from patients with SLE have been shown to have decreased levels of TCR protein and mRNA (2).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 99%